Tectonic Evolution of Granitoid Rock Granit Garba Based on Major Element in Tanjung Beringin, Muaradua, South OKU, South Sumatra - Aini, Salsyabillah Nurul; Hastuti, Endang Wiwik Dyah (Mataram University, 2022)
Granit Garba is one of the basements that make up the Garba Hills. Research on granitoid rocks that make up Granit Garba was carried out in the village of Tanjung Beringin and its surroundings, Muaradua District, South OKU Regency, South Sumatra Province. The formation of Granit Garba occurs due to the double subduction between Meso – Tethys with Woyla Arc and West Sumatra Block. The complete subduction of the Meso-Tethys plate then caused the collision between the two plates. The characteristics and tectonic evolution of the granitoid rocks were analyzed by conducting an XRF geochemical analysis of the major elements. The results of the analysis of the major elements of granitoid rocks have SiO2 content values ​​ranging from 63.71% to 69.55% it showing that Granit Garba is composed of quartz monzonite and granodiorite. The magma affinity of the two rocks is included in the calc-alkaline series with alumina saturation levels in the form of peraluminous and showing I-type granite.